2015
DOI: 10.1002/jhm.2529
|View full text |Cite
|
Sign up to set email alerts
|

The association between discharge before noon and length of stay in medical and surgical patients

Abstract: BACKGROUND Discharging patients before noon is a key approach to improving bed utilization. Few data exist to describe whether patients are discharged earlier or their stay is extended to allow for an early discharge the next day. OBJECTIVE To determine if a discharge before noon (DCBN) is associated with length of stay (LOS). DESIGN/SETTINGS/PATIENTS Retrospective analysis of data from adult medical and surgical discharges from a single academic center from July 2012 through April 2015. We used a multivariabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 3 publications
1
31
2
Order By: Relevance
“…4 These findings contrast with Rajkomar et al, who reported that DCBN was associated with a longer LOS in adult patients. 6 The contrasting findings could be due to differences in pediatric versus adult patients. Additionally, the population Rajkomar et al studied was predominantly surgical patients, whose discharges may differ from medical patients' in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…4 These findings contrast with Rajkomar et al, who reported that DCBN was associated with a longer LOS in adult patients. 6 The contrasting findings could be due to differences in pediatric versus adult patients. Additionally, the population Rajkomar et al studied was predominantly surgical patients, whose discharges may differ from medical patients' in many aspects.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a single, fixed discharge time target such as “discharge by noon” or “X% of discharges by 11:00A.M.” is becoming increasingly prevalent. Rajkomar, et al 7 recently reported a retrospective single institution review of discharge by noon, in which improvement in that metric was actually shown to be associated with increased acute care LOS. The authors concluded that focusing solely on a single metric alone was an insufficient approach.…”
Section: Discussionmentioning
confidence: 99%
“…4, 5 LOS also lacks the granularity to capture nuances of inpatient hospital admission patient flow which have implications for patient outcomes and staff work burden. 5, 6, 7 For example, a delay in discharge time from 11:00 a.m. to 7:00 p.m. does not cause an appreciable increase in the LOS. However, by decreasing bed availability, delays of this nature increase post-anesthesia care unit (PACU) and emergency department (ED) boarding times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, pre-noon discharges and provider-scheduled follow-up appointments may lead to unintended negative consequences and futility. 1,2 In contrast, weekend discharges, which were often viewed to be unsafe, may reduce lengths of stay without compromising care even in high-risk patients. 3 Having obfuscated the line between good and bad, we can now turn our attention to the ugly.…”
mentioning
confidence: 99%